"Bad and dangerous work": lessons from nineteenth- and early-twentieth-century oxford archives - Darwall-Smith, R; Riordan, M (Association of Canadian Archivists, 2012)
From the 1860s, Oxford colleges invited external scholars to catalogue their muniments. By looking at how eight colleges’ archives were arranged and described between 1860 and 1930, and by comparing them with the Dutch Manual and Jenkinson’s Manual, both published in this period, together with some earlier cataloguing work from eighteenth-century Oxford, this paper will show that a preoccupation not only with making the archives accessible but also with making particular records instantly available encouraged the archivists to ignore the provenance of records, breaking up fonds and organizing them according to chronology and subject matter rather than maintaining their original order. The consequence was that they treated the records in their care as discrete items, thus prejudicing content over context. The essay will also consider our own attitudes to archival management today, using a brief overview of government policies, archival theory, and online developments to suggest that, once again, we are concentrating solely on access and ignoring provenance. Finally, it will examine several online catalogues to explore whether, like our late-nineteenth- and early-twentieth-century forebears, we too are in danger of putting content before context.